The physiology and pharmacology of some cellulose derivatives - Wiedersheim, Robert Manfred (Division of Physiological Sciences, 2020)
Increasing knowledge in physics and chemistry has stimulated research on high polymers, or to use another term, on macromolecules and on their applications in various fields. The definition of macromolecules given in 1922 by Staudinger and Fritschi states that a macromolecule is a compound with more than 1,500 atoms and with a molecular weight exceeding 10,000; dissolved it shows colloidal properties and cannot be dialyzed.